2020
DOI: 10.2196/18751
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Smartphone-Recorded Environmental Audio and Symptomatology of Anxiety and Depression: Exploratory Study

Abstract: Background Objective and continuous severity measures of anxiety and depression are highly valuable and would have many applications in psychiatry and psychology. A collective source of data for objective measures are the sensors in a person’s smartphone, and a particularly rich source is the microphone that can be used to sample the audio environment. This may give broad insight into activity, sleep, and social interaction, which may be associated with quality of life and severity of anxiety and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 53 publications
4
36
0
2
Order By: Relevance
“…We note that any speech in the environment, including the playback of recorded speech, will be detected as speech; therefore, this feature is not a perfect proxy for social interaction. The results of the study by Di Matteo et al [30] were reported under the same conditions.…”
Section: Speech Presencesupporting
confidence: 66%
See 2 more Smart Citations
“…We note that any speech in the environment, including the playback of recorded speech, will be detected as speech; therefore, this feature is not a perfect proxy for social interaction. The results of the study by Di Matteo et al [30] were reported under the same conditions.…”
Section: Speech Presencesupporting
confidence: 66%
“…The speech presence feature is defined as the number of audio recordings labeled as containing speech divided by the total number of audio recordings. This feature was first proposed by Wang et al [15] and was confirmed to be a good correlate of anxiety and depression in our previous study [30]. We note that any speech in the environment, including the playback of recorded speech, will be detected as speech; therefore, this feature is not a perfect proxy for social interaction.…”
Section: Speech Presencementioning
confidence: 57%
See 1 more Smart Citation
“…This study used data collected in a previous study [ 4 ]. Participants were recruited from a web-based recruitment platform (Prolific [ 16 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Our prior efforts explored audio (nonlinguistic) features and correlates with mental health scales [ 4 ].…”
Section: Introductionmentioning
confidence: 99%